Identification of Essential Genes and Fluconazole Susceptibility Genes in Candida glabrata by Profiling Hermes Transposon Insertions. Issue 10 (1st October 2020) - Gale, Andrew N; Sakhawala, Rima M; Levitan, Anton; Sharan, Roded; Berman, Judith; Timp, Winston; Cunningham, Kyle W
Abstract: Within the budding yeasts, the opportunistic pathogen Candida glabrata and other members of the Nakaseomyces clade have developed virulence traits independently from C . albicans and C. auris . To begin exploring the genetic basis of C. glabrata virulence and its innate resistance to antifungals, we launched the Hermes transposon from a plasmid and sequenced more than 500, 000 different semi-random insertions throughout the genome. With machine learning, we identified 1278 protein-encoding genes (25% of total) that could not tolerate transposon insertions and are likely essential for C. glabrata fitness in vitro . Interestingly, genes involved in mRNA splicing were less likely to be essential in C. glabrata than their orthologs in S. cerevisiae, whereas the opposite is true for genes involved in kinetochore function and chromosome segregation. When a pool of insertion mutants was challenged with the first-line antifungal fluconazole, insertions in several known resistance genes ( e.g., PDR1, CDR1, PDR16, PDR17, UPC2A, DAP1, STV1 ) and 15 additional genes (including KGD1, KGD2, YHR045W ) became hypersensitive to fluconazole. Insertions in 200 other genes conferred significant resistance to fluconazole, two-thirds of which function in mitochondria and likely down-regulate Pdr1 expression or function. Knockout mutants of KGD2 and IDH2, which consume and generate alpha-ketoglutarate in mitochondria, exhibited increased and decreased resistance to fluconazole through a process that depended on Pdr1. These findings establish the utility of transposon insertion profiling in forward genetic investigations of this important pathogen of humans.